Photosynthetic generation of heterologous terpenoids in cyanobacteria. Issue 8 (20th April 2019) - Betterle, Nico; Melis, Anastasios
Abstract: The work aims to convert the secondary slow metabolism of the terpenoid biosynthetic pathway into a primary activity in cyanobacteria and to generate heterologous products using these photosynthetic microorganisms as cell factories. Case study is the production of the 10‐carbon monoterpene β‐phellandrene (PHL) in Synechocystis sp. PCC 6803 ( Synechocystis ). Barriers to this objective include the slow catalytic activity of the terpenoid metabolism enzymes that limit rates and yield of product synthesis and accumulation. " Fusion constructs as protein overexpression vectors " were applied in the overexpression of the geranyl diphosphate synthase ( GPPS ) and β‐phellandrene synthase ( PHLS ) genes, causing accumulation of GPPS up to 4% and PHLS up to 10% of the total cellular protein. Such GPPS and PHLS protein overexpression compensated for their slow catalytic activity and enabled transformant Synechocystis to constitutively generate 24 mg of PHL per g biomass (2.4% PHL:biomass, w‐w), a substantial improvement over earlier yields. The work showed that a systematic overexpression, at the protein level, of the terpenoid biosynthetic pathway genes is a promising approach to achieving high yields of prenyl product biosynthesis, on the way to exploiting the cellular terpenoid metabolism for commodity product generation. Abstract : The work aims to convert the secondary slow metabolism of the terpenoid biosynthetic pathway into a primary activity in cyanobacteria, and to generate heterologous products using these photosynthetic microorganisms as cell factories. Case study is the production of the 10‐carbon monoterpene β‐phellandrene (PHL) in Synechocystis sp. PCC 6803 ( Synechocystis ). Barriers to this objective include the slow catalytic activity of the terpenoid metabolism enzymes that limit rates and yield of product synthesis and accumulation.